STUDI PEMBUATAN MINYAK KELAPA MURNI SECARA ENZIMATIS DENGAN MENGGUNAKAN BERBAGAI TINGKAT KONSENTRASI ENZIM NANAS PADA DUA JENIS KELAPA - Prihanani Prihanani; Danner Sagala; Yondi Yonadi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2013)
Virgin coconut oil can be proccessed in many ways to meet market quality. One of them is enzymaticly process. The aim of this research was to know bromelin enzyme concentration on two varieties of coconut. The experiment was conducted at PT. Sandabi Indah Lestari laboratory, Lunjuk Village, Seluma Barat Subistrict and Seluma Regency from in July 2012. The experiment was arranged in completely randomized design with two factos and three replication. The first faktor was variety of coconut consisted of Kelapa dalam and Kelapa hibrida. The second factor was bromelin enzyme concentration consisted of LIPI enzyme (as control), 50, 100, 150 gram. Variety affected most significantly on virgin coconut oil rendement. Kelapa dalam variety produced the higher virgin coconut oil than kelapa hibrida variety. However, variety and enzyme were affected unsignificant on water content of the virgin coconut oil.